Electrical responses of graphene layers to extrinsic charges - Shi, Yu Meng (2010)
Graphene has attracted great interest due to their unique electronic structures, physical properties and geometries. Graphene thin layers are very sensitive to the environmental perturbations including heat, photons and charges. With a relatively large cross section for readily receiving molecules or interacting with environmental charges, graphene exhibits greater potential for practical applications in biomolecular sensors, nonvolatile memory cells, solar cells, photo detectors and etc. Among all of these applications, graphene layers act as a charge sensor or a charge collector. Therefore, better understanding of the charges interaction with this carbon material is crucial. In this thesis, we investigate electrical responses of graphene layers to the extrinsic charges and utilize the charge doping effects to extend the application of graphene layers in photoelectronics. For graphene electronic devices, graphene layers were typically in direct contact with the dielectric layers. Owing to their high sensitivity to environmental perturbations, it is necessary to consider the contribution of the extrinsic carriers from the underlying substrates. We first studied the charge doping effect of the supporting substrates to single layer graphene (SLG) by electrostatic force microscopy (EFM), Raman spectroscopy and electrical characterizations. It was found that the SLG can be effectively doped by the underlying materials, which results in a modulation of electronic property.